Anti-aging versus positive-aging language in scientific literature: Raising questions for future research - Akbar Azizi-Zeinalhajloo; Haidar Nadrian; Nafiseh Ghassab-Abdollahi; Elham Lotfalinejad; Hassan Rezaeipandari; Devender Bhalla (BioSocial Health Journal)
Ageism is one of the most common forms of discrimination among older adults. Although applicable in regards to discrimination against all age groups, the term ageism is predominantly used in relation to the treatment of older people. Anti-aging language refers to the use of words, phrases and sentences when talking with or about older adults. Terms such as "old people," "old age," "elderly", "the elderly" and "the aged" are in the form of anti-aging speaking, and it is recommended that the terms "older people", "older adults", "seniors" and "later life" be used instead of the latter mentioned terms, indicating there is a growing sense that emphasis on a positive perception and illustration of aging. There is a lack of evidence on the diversity, frequency, range of terms and expressions and examples of anti-aging speaking, and also the other end, positive aging. In this perspective study, we raised questions to address the existing gap, with the hope to help future researchers in the use of negative/positive semantic words or negative/positive attitudes towards the older adults and examples of anti-aging/positive aging speaking in scientific texts. Raising such research questions might be useful in capturing the spirit of the field and some of its focus, and revealing how scientists talk about aging, or whether they use or are trying to combat ageist language.